2021
DOI: 10.3390/curroncol28020116
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-618 Has Prognostic Significance in Patients with Metastatic Colon Cancer

Abstract: The present study evaluated the prognostic role of circulating miRNA-618 in patients with metastatic colon cancer (mCC) and whether miR-618 gene rs2682818 single nucleotide polymorphisms (SNP) are associated with colon cancer susceptibility and expression levels of mature miR-618. In total, 104 patients with mCC before starting the chemotherapy were investigated. The expression status of circulating miR-618 in mCC was evaluated by quantitative PCR. TaqMan PCR assay was used for rs2682818 SNP genotyping. miR-61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Rs2682818 is located in the hairpin-loop structure of the miR-618 precursor, which may affect the process of miR-618 interaction with its target [ 98 ]. Our recent study showed that the deregulated expression of the circulating miR-618 in Caucasian patients with colon cancer was not altered because of rs2682818 variants [ 99 ]. We also found that rs2682818 AC genotype was associated with a decreased risk of colon cancer.…”
Section: Single Nucleotide Polymorphisms (Snps) In Genes For Mirnas Associated With Colorectal Cancer (Crc) Riskmentioning
confidence: 99%
“…Rs2682818 is located in the hairpin-loop structure of the miR-618 precursor, which may affect the process of miR-618 interaction with its target [ 98 ]. Our recent study showed that the deregulated expression of the circulating miR-618 in Caucasian patients with colon cancer was not altered because of rs2682818 variants [ 99 ]. We also found that rs2682818 AC genotype was associated with a decreased risk of colon cancer.…”
Section: Single Nucleotide Polymorphisms (Snps) In Genes For Mirnas Associated With Colorectal Cancer (Crc) Riskmentioning
confidence: 99%
“…The potential usefulness of other circulating miRNAs as biomarkers of mCRC has been extensively studied [1,12,24] MiR-203, miR-618, and miR-200c in serum were identified as promising biomarkers to predict metastasis [15,25,31,32]. These studies also showed the aberrant expression of miR-203 along the individual stages of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Low expression of circulating miR-618 in patients suffering from metastatic CRC is connected with shorter overall survival. The results of this study indicate that the level of miR-618 in the blood can be tested as a prognostic biomarker in patients with metastatic CRC [ 152 ].…”
Section: Role Of Selected Micrornas In Gastrointestinal Cancersmentioning
confidence: 99%